Health and Schooling Investments in Africa - T. Paul Schultz (Yale University, Economic Growth Center, 1999)
Regressions across countries from 1960 to 1995 are discussed to document African poor performance in terms of infant and child mortality, life expectation, and school enrollment rates, controlling for national income, women's and men's schooling, and urbanization. It is concluded that intercountry regressions do not yet help us determine the consequences of this shortfall in these forms of human capital investments on the region's economic growth. The paper then examines microeconomic estimates based on household surveys of the productive payoff in Sub-Saharan Africa to nutrition and health, as proxied by adult height and weight-for-height, and to education, proxied by years of schooling completed, by level. Biases due to household heterogeneity and sample selection are assessed in the cases of Ghana and Cote d'Ivoire. Political restrictions in South Africa before 1993 are interpreted as accounting for the low levels of educational attainment of nonwhites, and these quotas offer a supply explanation for the corresponding high rates of return to secondary and post-secondary schooling for those nonwhites who still managed to obtain such an education. Studies evidence is then considered on the wage returns to variation in the local quality of schooling, which appear to benefit disproportionately the above-average income households in Africa, as in most other low-income settings.
Keywords: 330; Africa; Schooling; Health; Returns; Quality; Humankapital; Bildungsertrag; Bildung; Gesundheit; Wirtschaftswachstum; Zentralafrika